A Taxonomy of Principles Used in Judo Throwing Techniques - Yiannakis, Linda (Revista de Artes Marciales Asiáticas, 2012)
This paper presents a conceptual framework for examining principles of judo throwing techniques (nage-waza). The principles formulated in this study are classified as primarily structural, operational, or contextual in nature. Such an organization of properties allows a clearer examination of the operation of throwing techniques for the purpose of identification, teaching, and innovation. This framework was developed from the author’s personal observations and understanding of throwing principles. This way of thinking about throwing principles may be useful for examining techniques in other martial arts as well.